Use of anticholinergics and the risk of cognitive impairment in an African American population - Campbell, N L; Boustani, M A; Lane, K A; Gao, S; Hendrie, H; Khan, B A; Murrell, J R; Unverzagt, F W; Hake, A; Smith-Gamble, V; Hall, K (Neurology, 2010)
Anticholinergic properties of certain medications often go unrecognized, and are frequently used by the elderly population. Few studies have yet defined the long-term impact of these medications on the incidence of cognitive impairment. We report a 6-year longitudinal, observational study, evaluating 1,652 community-dwelling African American subjects over the age of 70 years who were enrolled in the Indianapolis-Ibadan Dementia Project between 2001 and 2007 and who had normal cognitive function at baseline. The exposure group included those who reported the baseline use of possible or definite anticholinergics as determined by the Anticholinergic Cognitive Burden scale. Our main outcome measure was the incidence of cognitive impairment, defined as either dementia or cognitive impairment not dementia, or poor performance on a dementia screening instrument during the follow-up period. At baseline, 53% of the population used a possible anticholinergic, and 11% used a definite anticholinergic. After adjusting for age, gender, educational level, and baseline cognitive performance, the number of definite anticholinergics was associated with an increased risk of cognitive impairment (odds ratio [OR] 1.46, 95% confidence interval [CI] 1.07-1.99; p = 0.02), whereas the number of possible anticholinergics at baseline did not increase the risk (OR 0.96, 95% CI 0.85-1.09; p = 0.55). The risk of cognitive impairment among definite anticholinergic users was increased if they were not carriers of the APOE epsilon4 allele (OR 1.77, 95% CI 1.03-3.05; p = 0.04). Limiting the clinical use of definite anticholinergics may reduce the incidence of cognitive impairment among African Americans.